Effect of phospholipid head group on ultrasound‑triggered drug release and cellular uptake of immunoliposomes - Awad, Nahid S. (2023)
Liposomes are the most successful nanoparticles used to date to load and deliver chemotherapeutic agents to cancer cells. They are nano-sized vesicles made up of phospholipids, and targeting moieties can be added to their surfaces for the active targeting of specific tumors. Furthermore, Ultrasound can be used to trigger the release of the loaded drugs by disturbing their phospholipid bilayer structure. In this study, we have prepared pegylated liposomes using four types of phospholipids with similar saturated hydrocarbon tails including a phospholipid with no head group attached to the phosphate head (DPPA) and three other phospholipids with different head groups attached to their phosphate heads (DPPC, DPPE and DPPG). The prepared liposomes were conjugated to the monoclonal antibody trastuzumab (TRA) to target the human epidermal growth factor receptor 2 (HER2) overexpressed on HER2-positive cancer cells (HER2+). We have compared the response of the different formulations of liposomes when triggered with low-frequency ultrasound (LFUS) and their cellular uptake by the cancer cells. The results showed that the different formulations had similar size, polydispersity, and stability. TRA-conjugated DPPC liposomes showed the highest sensitivity to LFUS. On the other hand, incubating the cancer cells with TRA-conjugated DPPA liposomes triggered with LFUS showed the highest uptake of the loaded calcein by the HER2+ cells.